2013
DOI: 10.12816/0006023
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Keratoplasty for Keratoconus : Visual and Graft Survival Outcomes

Abstract: Objectives: To evaluate the complications, and visual and graft survival outcomes in eyes that had undergone penetrating keratoplasty (PKP) for keratoconus. Methodology: This restrospective study includes 311 patients with keratoconus who had undergone PKP between January 1, 2001, and December 31, 2002, at King Khaled Eye Specialist Hospital. All patients were followed up postoperatively (maximum follow-up, 65.77 months). Results:The mean age of patients with keratoconus at transplantation was 23.72 years. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The BCVA with hard contact lens of 29 eyes without amblyopia in our study was 20/27. This result is similar to the results of previous studies, with the BCVA ranged from 20/25 to 20/32 [7], [8], [11], [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The BCVA with hard contact lens of 29 eyes without amblyopia in our study was 20/27. This result is similar to the results of previous studies, with the BCVA ranged from 20/25 to 20/32 [7], [8], [11], [13].…”
Section: Discussionsupporting
confidence: 92%
“…The successful rate of PK for keratoconus is higher than other diseases. After 5 to 12 years, the graft survival rate is more than 90% [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…(11) Similarly, Dandona et al reported a 95.1% survival rate at 5 years (12). Immune rejection is the most common cause of graft failure after PKP (10,13). In our study, all 3 graft failures were secondary to graft rejection.Among the donor-related risk factors in our study, donor age was not associated with an increased risk of rejection.…”
supporting
confidence: 71%
“… 21 Postoperative visual acuity of 20/20 to 20/40 was noted in 68% of 311 eyes with keratoconus that had undergone primary PKP. 22 This rate further declined when PKP was performed to manage failed graft with functional vision in only 4.8% of eyes. 23 The learning curve among postgraduate students at our teaching institute could be an alternative explanation of lower outcomes with PKP.…”
Section: Discussionmentioning
confidence: 99%